Study of Excess Volumetric and Thermodynamic Properties and Viscosity Modeling for Binary Liquid Mixtures of Isopropyl Benzene (cumene) with Aromatic Hydrocarbons at Temperature 298.15 K and Under Atmospheric Pressure - Sharma, Dhirendra Kumar; Prajapati, Chandra Pal; Kumar, Suneel (European Journal of Applied Sciences, 2026)
The present discussion embodies the studies on binary mixtures containing isopropyl benzene (cumene) + ethyl benzene, isopropyl benzene (cumene) + toluene, isopropyl benzene (cumene) + mesitylene, isopropyl benzene (cumene) + n-propyl benzene, isopropyl benzene (cumene) + tert-butyl benzene, and isopropyl benzene (cumene) + biphenyl at the 298.15 K. For this purpose, the density, viscosity and speed of sound for pure liquids and their binary mixtures were measured within the temperature range 298.15K. Various excess and deviation parameters have been calculated using the measured properties. These properties provide valuable insight into molecular interactions and help predict the behaviour of complex chemical systems. Excess and deviation parameters were fitted to the Redlich−Kister polynomial.